Upaya Peningkatan Hasil Belajar dan Keaktifan Berbantu Media Puzzel pada Materi Bangun Datar Kelas II SD - Aufa, Farchana Nur; Wulandari, Murfiah Dewi; H, Mila Ary (FONDATIA, 2024)
This research aims to address issues occurring in the teaching process in class II of SD N Wirogunan 03 Kartasura, where mathematics instruction still follows a conventional model involving only teacher-led delivery without any real activities to aid students' understanding of the material. The proposed solution is to use puzzle-based learning media to enhance learning outcomes and student engagement in the learning process. This study employs the Classroom Action Research (CAR) method, comprising two cycles with a pre-cycle followed by planning, implementation, observation, and reflection stages. Evaluation of learning outcomes and student engagement is conducted using assessment sheets and observations. The research findings indicate that the use of puzzle-based learning media improves learning outcomes and student engagement. The percentage of learning outcomes in the pretest was 27.2%, increased to 54.6% in cycle I, and reached 81.9% in cycle II. Furthermore, student engagement in the pretest was 36.3%, increased to 63.7% in cycle I, and reached 100% in cycle II. From these research findings, it can be concluded that the use of puzzle-based media effectively enhances learning outcomes and student engagement, creating active and engaging learning experiences.